1991
DOI: 10.1007/bf01977358
|View full text |Cite
|
Sign up to set email alerts
|

Tactile-kinesthetic system of rats as an animal model for minimal brain dysfunction

Abstract: A previous study showed that rats exposed to methylmercury during development exhibit effects similar to those described for children with minimal brain dysfunction (MBD), namely, hyperactivity, altered locomotion structure, and unaltered learning ability, but reduced and more variable attention spans induced by increasing difficulties within an operant learning paradigm. Psychopathological studies suggest that behavioral disturbances of the MBD type may originate directly or indirectly from deficiencies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 24 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Similarly, exposure to 0.10 mg/kg/day MeHg hydroxide from gestation to PND 55 resulted in diminished motor function overall. Thus, these chronic Hg exposure studies are consistent with the shorter exposure study by Elsner (1991) included in Fig. 3.…”
Section: Review Of Toxicological Profilessupporting
confidence: 85%
“…Similarly, exposure to 0.10 mg/kg/day MeHg hydroxide from gestation to PND 55 resulted in diminished motor function overall. Thus, these chronic Hg exposure studies are consistent with the shorter exposure study by Elsner (1991) included in Fig. 3.…”
Section: Review Of Toxicological Profilessupporting
confidence: 85%
“…On the other hand, more mechanistic analyses of these behaviors might reveal the inherent sensitivities of these tests, which would support the former explanation. It should also be noted that the reproducibility of these test results must be demonstrated; e.g., Elsner (40) could not reproduce the deviation in the spatial alternation task (30) obtained in their first trial, and no laboratory has published rodent behavioral studies that showed effects from the same low level of exposure as was demonstrated in the DRH studies (39).…”
Section: Studies In Nonhuman Primatesmentioning
confidence: 99%
“…For example, the results of the discrete trial spatial alternation task used by Eisner et al (30) were compared to the attention disorder (and minimal brain dysfunction) seen in human children. Testing the tactile-kinesthetic system of rats (40) was suggested by human studies that showed a relationship between attention deficit disorder and poor development of the tactile-kinesthetic system in children. If such a functional analogy could be validated with some appropriate experiments, this type of approach could provide a means to directly predict human behavior on the basis of rodent behavior.…”
Section: Development Of Specific Test Batteriesmentioning
confidence: 99%
“…Among others, the spatial alternation test (30), the tactilekinesthetic test (40), and the DRH task (39) showed deviations from control at very low dose levels, At these doses, other simple tests such as those included in a functional observation battery, would fail to show any changes. It is unknown, however, whether such differential sensitivities among the tests reflected the nature of the behavioral tasks per se or reflected the nature of the effect of methylmercury.…”
Section: Studies In Nonhuman Primatesmentioning
confidence: 98%
“…6.4 x 1 (gi) GD 15 "Step-down" passive avoidance 60 Rapid extinction (35) Abbreviations: iv, intravenous injection; sc, subcutaneous injection; gi, gastric intubation; GD, day(s) of gestation. (40) trained rats to press a lever with predetermined ranges of force and time. The impaired performance of methylmercury-exposed rats was considered to be a result of deficit in tactile-kinesthetic systems.…”
Section: Recent Epidemiological Studiesmentioning
confidence: 99%